Implementation Of Local Wisdom Of Serakalan Tradition In Strengthening Islamic Religious Education In The Mapak Dasan Environment, Jempong Baru Village, Sekarbela District, Mataram City - Irwan Irwan; Nursidi Nursidi; Ahmad Khaerul Kholidi; Syarifudin Syarifudin; Abdul Kohar (Pusat Penelitian dan Pengabdian kepada Masyarakat Sekolah Tinggi Agama Islam Nahdlatul Wathan Samawa Sumbawa Besar, 2024)
This research aims to determine the implementation of local wisdom in strengthening Islamic values. So far, residents of the Mapak Dasan neighborhood have been able to implement the cultural traditions of local wisdom, Selakaran, to form an Islamic character, this has been carried out at sacred events, namely at the Selakaran Nyunatan event, Friday night Selakaran at the local neighborhood mosque, Selakaran Ngurisan, Selakaran Selamat Rumah, Selakaran At the time of departure of prospective pilgrims, remembrance of the times, etc., these local wisdom cultural traditions can be felt to be able to form an Islamic character in facing the current era of globalization in the modern era. This research uses a qualitative case study type method and uses research techniques, namely observation, interviews and documentation. Data analysis was carried out by data reduction, data display, and conclusion drawing/verification. This research shows that the local wisdom cultural traditions in question are able to form an Islamic golden generation, because the traditions that have developed in the Mapak Dasan environment are traditions that have been passed down from generation to generation from their ancestors and are able to form an Islamic generation so that the strengthening of Islamic values ​​can be reflected in the lives of local residents. Keywords: Local Wisdom, Strengthening Islamic Religious Values, Mapak Environment.